PENGAWETAN UMBI BAWANG MERAH DENGAN RADIASI GAMMA CO-60 - Purwanti, Titik; Sutapa, Gusti Ngurah; Trisnawati, Ni Luh Putu (BULETIN FISIKA; Vol 14 No 2 (2013): BULETIN FISIKA, 2013)
Onion (Allium ascalonicum L) Preservation With Gamma Ray Co-60.This experiment has been done to find out approach optimum dose that able to resist the growing of onion bud. The response that exceeded is morfology through the growing of onion bud. The onion that is used is from Thailand variety with 5 month and average weight is 4.15 gramsfor 650 pieces. 650 pieces of onion irradiated by using gamma ray Co-60 IRPASENA irradiator at PTKMR BATAN, Pasar Jumat Jakarta. Iradiation dose is varieted by 50 Gy, 100 Gy, 150 Gy, and 200 Gy. Bud onion growing exceeded and documented once a week, and room temperature and room humidity noted once a day. During 2 months experiment have been found the result that irradiated onion with 150 Gy dose have the slowest growing compare to other variety dose compared by 50 Gy, 100 Gy, 150 Gy and 200 Gy.